2012
DOI: 10.4236/wjnse.2012.24026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evaluation of Antibacterial Activities of Chemically Synthesized Iron Oxide Nanoparticles

Abstract: The iron oxide nanoparticles have been synthesized in co-precipitation method using aqueous solution of ferric and ferrous ions with sodium salt. The synthesis of iron-oxide nanoparticles were validated by UV-Visible spectroscopy which showed higher peak at 370 nm as valid standard reference. An average size of iron oxide nanoparticle found by Diffraction Light scattering (DLS) particle size analyser, ranges approximately between 10 nm to 120 nm with mean particle size of 66 nm. The X-ray power diffraction (XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(103 citation statements)
references
References 15 publications
8
95
0
Order By: Relevance
“…One Tof the magnetic nanoparticles is Fe 3 O 4 (magnetite). The materials exhibit superparamagnetic behavior, low toxicity, biocompatibility, easier surface modification [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One Tof the magnetic nanoparticles is Fe 3 O 4 (magnetite). The materials exhibit superparamagnetic behavior, low toxicity, biocompatibility, easier surface modification [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The Fe 3 O 4 nanoparticle has the greatest antibacterial effect to pathogenic bacteria of Pseudomonas aeroginosa than Escherichia coli and Staphylococcus aureus [15]. In addition, Fe 3 O 4 nanoparticle has a zone of inhibition consideration to Ag nanoparticle for topical use [14]. Materials in the form of small particle sizes are easy to agglomerate and made it larger particle size, reducing surface area and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Viability, growth Pseudomonas aeruginosa [26] MNPs/Ag/chitosan Viability Pseudomonas aeruginosa [39] MNPs stabilized with thioglycerol Viability, growth Pseudomonas aeruginosa [45] MNPs coated with vancomycin, penicillin and streptomycin Adherence, biofilm formation Enterococcus faecalis [47] MNPs/Ag/chitosan Viability, growth Enterococcus faecalis [39] dextran MNPs coated with amino acids (L-arginine and L-lysine) Viability, growth Listeria monocytogenes [49] MNPs stabilized with thioglycerol Viability, growth Bacilus subtilis [45] 66 nm of iron oxide MNPs Viability, growth Bacilus subtilis [48] 66 nm of iron oxide MNPs Viability, growth Bacilus licheniformis [48] 66 nm of iron oxide MNPs Viability, growth Bacilus brevis [48] 66 nm of iron oxide MNPs Viability, growth Vibrio cholerae [48] 66 nm of iron oxide MNPs Viability, growth Streptococcus aureus [48] An example of the mechanism by which MNPs functionalized with antibiotics improve the antimicrobial inhibition is illustrated in Figure 3. Like the antibiotics which act by interrupting the cell wall synthesis (Figure 3a), studies have revealed that magnetite nanoparticles coated with a chitosan polymeric matrix are able to also bind to bacterial cell walls and interrupt its synthesis.…”
Section: Enterococcus Faecalismentioning
confidence: 99%
“…Viability, growth Staphylococcus aureus [26] MNPs/Ag/chitosan Viability, growth Staphylococcus aureus [39] MNPs stabilized with thioglycerol Viability, growth Staphylococcus aureus [45] 66 nm of iron oxide MNPs Viability, growth Staphylococcus aureus [48] MNPs/chitosan/ aminoglycosides (kanamycin and neomycin) Viability, growth Pseudomonas aeruginosa [27] Spherical MNPs coated with eugenol Adherence, biofilm formation Pseudomonas aeruginosa [46] MNPs/chitosan/carboxymethylcellulose/ antibiotics (penicillins, macrolides, aminoglycosides, rifampicines quinolones)…”
Section: Enterococcus Faecalismentioning
confidence: 99%
“…Yuvakkumar et al [24] prepared nano-scaled zero valent iron (50−100 nm) using the reduction method based on the use of ferric ions and sodium borohydride in ethanol under atmospheric conditions. Behera et al [25] also prepared iron oxide NPs for antibacterial applications using co-precipitation method. Lee et al [26] investigated the synthesis of iron oxide nanomaterials in microfluidics device under ambient conditions with the use of co-precipitation method.…”
Section: Introductionmentioning
confidence: 99%